Facebook and sport education: mirroring the model at home to promote parental involvement. Issue 8 (13th October 2019) - Fernandez-Rio, Javier; Bernabe-Martín, Javier
ABSTRACT: Social networks had become so important that they constitute a way of life for many individuals, and Facebook is probably the most popular one. Society has become totally connected, but classrooms still remain rather isolated. The goal of the study was to extend the Sport Education Model (SEM) through a social network, Facebook, to promote parental involvement, assessing its impact at home. 41 parents of 49 grade 12th secondary education students agreed to participate (39−57 years): 14 fathers and 27 mothers. The vast majority of participating parents that included information about their socio-economic and educational background considered themselves medium level (11 out of 13). Unfortunately, most parents did not provide this type of information (69.30%). An AcroGymnastics learning unit was implemented using the SEM during 16 sessions. All Facebook activity was recorded by the site, and semi-structured interviews were used to obtain data directly from the parents. Quantitative data was analysed using Gytrics, while MAXQDA 11 helped with qualitative data management. Quantitative results showed that the Facebook group had a notable effect in parents' involvement: 42.26% joined (67% mothers), 100% reacted, 70.47% published content, 48.69% uploaded a picture/video, 503 posts, 14, 528 hits, and 2025 reactions: 1912 likes and 113 comments. Themes derived from the analysis of the qualitative data reinforced the idea that Facebook helped promote parental participation: involvement, affiliation and learning, and some SEM features at home: affiliation, festive atmosphere and participation . Finally, a change in the PE status was also observed among parents. In conclusion, the combination Facebook-SEM had a notable positive effect on parental involvement, especially among mothers of medium socio-economic background. The number and type of activities posted by the administrator seemed to be a key element to positively integrate Facebook in education.